Aspectos competitivos em espécies florestais: interferência de plantas daninhas e de brotações indesejadas - Leandro Roberto da Cruz (2014)
Knowledge of the degree of weed interference on forest species is critical to maintenance of productivity and development mainly in its early stages. In eucalyptus cultivation, when the renewal of his budding after shallow cutting of the tree, the buds themselves can compete with the main stem. The control of unwanted buds has raised doubts about the efficiency of the techniques used and by the possible poisoning by glyphosate. The referred study aims to: 1- evaluate the effects of interference of spiderwort (Commelina benghalensis) and grass braquiarão (Brachiaria brizantha) on the morphological and physiological characteristics and in the bioaccumulation of nutrients of the mahogany African (Khaya ivorensis). 2- evaluate the growth and the quality of eucalyptus wood when of the mechanical sprout thinning or with the use of glyphosate. In trial 1 the African mahogany was grown in coexistence with C. benghalensis or with B. brizantha in different densities, in an experimental design of randomized blocks in a factorial scheme 2x6, being the factor I represented by both weeds and the factor II for six weed densities (0, 1, 2, 3, 4 and 5 plants / pot or 0, 14, 28, 42, 56 and 70 plants / m2). In trial 2 were tested different methods of controlling of the unwanted budding of eucalyptus in clonal planting with six months after shallow cutting of trees. The trial was arranged in a randomized block design with four replications, with seven treatments for the control of unwanted budding of the eucalyptus, as follows: control (absence of control), control with sickle, spade, application 360, 720, 1080 or 1440 g ha-1 of glyphosate. For physical and chemical analysis of the wood were cut plants according to the range of intoxication by glyphosate (control, 1-15, 16-30, 31-45 and 46-60% intoxication) with eight replicates per group. To characterization of the chemical compounds of the extractive were chosen for comparison and descriptive analysis chromatograms in poisoning rates 0 (control), 16-30 and 45-60%. The B. brizantha promoted negative interference on morphophysiology of the African mahogany independent of the evaluated density. The C. benghalensis influenced negatively the morphological parameters and presented with less potential harmful for the African mahogany, compared to B. brizantha. The African mahogany suffered a decrease of nutrient in its aerial part and smaller accumulation of biomass in coexistence with the weeds in question for both macro and micronutrients. The increased density of weeds in coexistence with African mahogany increases interference between the species and negatively affects the individual biomass of the weeds, proving the occurrence of intraspecific competition. The mechanical control of unwanted budding in eucalyptus trees surpassed the chemical control on volume of wood produced per hectare. Eucalyptus trees subjected to chemical control of unwanted budding showed symptoms of poisoning by the herbicide and lower growth, with plants recovery trend over time. The control methods did not interfere in the density and in content of extractives of the eucalyptus wood, however, were observed small changes in the chemical characterization of the extractive of trees that showed poisoning by glyphosate. The Mahogany African presents morphophysiological damage, lower growth and a decrease in the accumulation of nutrients when in coexistence with weeds. This interference increases with increased density of the weed species, and the B. brizantha showed to be more aggressive in relation to C. benghalensis. The mechanical control of budding promotes higher productivity in relation to chemical control which in turn caused poisoning in the main stem regardless of the dose used in eucalyptus plants. The physico-chemical characteristics of the wood did not change in eucalyptus intoxicated by glyphosate. There was variable response in the chemical composition of the extractive in function of the of intoxication tracks.